Metabolic alterations in liver of fresh water fish, C. punctata exposed to arsenic: an adverse and adaptive response to the environment (International Journal of Agricultural Research, Innovation and Technology, 2017)
Arsenic is a major toxicant impairing in diverse metabolic alterations of the organisms and the mechanism of adaptive response is yet to be identified. In the present study, effects of different doses of arsenic in liver of Channa punctata on the regulation of metabolic activities were done. C. punctata, a variety of fresh water fish were exposed to 1, 10 and 1000 ?M concentration of Na2HAsO4 for 1 h. The amount of protein, in response to 1, 10 and 1000 ?M concentration of arsenic were augmented by 184.47% (2.84-folds), 202.82% (3.0- folds) and 317.49% (4.17-folds), respectively and was found to be higher for 1000 ?M dose. Cholesterol contents in liver were similarly exaggerated by 517.45% (6.17-folds), 308.13% (4.1-folds) and 286.41% (3.86-folds), respectively. However, the higher response was found for 1 ?M dose of Na2HAsO4. Similar stimulatory effects on triglyceride level were observed in response to arsenic. Na2HAsO4 causes 443.74% (5.43-folds), 533.11% (6.33-folds) and 548.48% (6.48-folds) enhanced triglyceride level in liver respectively and the effects were pronounced for 1000 ?M concentration. Our findings conclude that arsenic is involved in impairment of metabolic activities in liver of the species of fish and gives an impact to the environment for survival.Int. J. Agril. Res. Innov. & Tech. 6 (2): 87-94, December, 2016